Environment and global modernity - Spaargaren, Gert.; Mol, A. P. J.; Buttel, Frederick H.; Sage eBooks (London : SAGE, 2000)
Taking a global perspective, this book argues that we can only make sense of environmental issues if we consider them as part of a more encompassing process of social transformation.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Global environmental change -- Congresses; Social change -- Congresses; Globalization -- Congresses; Electronic books